Failures in implantology: literature review. - Calazares, Andrew Jorge; Mesquita Araujo, Cintia (Brazilian Journal of Implantology and Health Sciences, 2020)
The increasing number of implants placed on patients all over the world shows the importance of this technique, which restores quality of life to people who have tooth loss, aiming at reducing costs and facilitating access to treatment already established for having less than 6% of failure. The knowledge of the failures is of fundamental importance for the search to improve the quality of this treatment and the different protocols and techniques make its success probable. Our work aimed, through the literature review, to unite information contained in books and physical and digital articles about the possible causes that lead the treatment with implants to not have the expected success and with this make more evident what must be done to avoid failure . It was clear from our work that the dentist, equipped with his knowledge, is able to increase the chances of success in implantology by performing a good assessment of the general conditions of the patient and places where the implant will be placed. The choice of the implant is also fundamental, as well as the technique used correctly to insert the screw into the bone. Biosafety during the procedure by the dentist and perfect hygiene by the patient in the postoperative period increase the chances of a good prognosis.